2002
DOI: 10.1007/s00520-002-0383-y
|View full text |Cite
|
Sign up to set email alerts
|

Important aspects of care and assistance for children 0–7 years of age being treated for cancer

Abstract: Aspects of care and assistance that are important for children aged 0-7 years who are being treated for cancer were examined. Parents ( N=57) and nurses ( N=59) were asked: "What caring aspects are important in ensuring that your child/the child feels cared for?" and "What help, if any, does your child/the child need outside the hospital?". Data were analysed by content analysis. The following aspects of care were identified: amusement, clinical competence, continuity, emotional support, family participation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Runeson et al (2002) showed that the child had a need to have the parent nearby, especially in threatening situations. In the light of the findings from the present study and earlier studies (Cleary et al, 1986;Runeson et al, 2002), it is important to highlight the significant role played by parents during a child's hospitalization and cancer treatment, especially because von Essen et al (2002) showed that the parents did not seem to attach high value to their own or other family members' presence at the ward or their involvement in the child's care.…”
Section: Discussionmentioning
confidence: 84%
“…Runeson et al (2002) showed that the child had a need to have the parent nearby, especially in threatening situations. In the light of the findings from the present study and earlier studies (Cleary et al, 1986;Runeson et al, 2002), it is important to highlight the significant role played by parents during a child's hospitalization and cancer treatment, especially because von Essen et al (2002) showed that the parents did not seem to attach high value to their own or other family members' presence at the ward or their involvement in the child's care.…”
Section: Discussionmentioning
confidence: 84%
“…This is encouraging since it has been reported that parents of children with cancer perceive the staff's clinical competence as highly important in order to assure that their child is well cared for (Enskär & von Essen 2000;von Essen et al 2002). This is encouraging since it has been reported that parents of children with cancer perceive the staff's clinical competence as highly important in order to assure that their child is well cared for (Enskär & von Essen 2000;von Essen et al 2002).…”
Section: Discussionmentioning
confidence: 89%
“…High satisfaction was reported with nurses' interpersonal skills, somewhat less with doctors' interpersonal skills. It has been shown that information about disease and treatment, according to parents, is important in order to make children with cancer feel well cared for (Enskär & von Essen 2000;von Essen et al 2002). This may be explained by nurses spending more time with patients and/or that nurses are more educated and focused on providing psychosocial care.…”
Section: Discussionmentioning
confidence: 99%
“…Answers to the open‐ended questions were tape recorded, transcribed, and analysed by means of content analysis, which can be used to draw valid conclusions about a manifest message in a communication by systematic identification of specified communication characteristics 34. The analysis was performed in the following steps 35: (1) The first author read the transcribed text several times. (2) Words and sentences (recording units) containing information about how the respondent coped with the four areas of distress were identified (by the first and second author).…”
Section: Methodsmentioning
confidence: 99%